(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
In this article theoretical studies of DESO–H2O molecular complexes by ab initio quantum-chemical calculation is presented. From the vibrational spectroscopic studies of diethylsulfoxide water solutions the possibility of formation of DES0–H2O(I) and DESO–H2O(II) complexes is developed. By ab inintio quantum-chemical calculations the existence of these complexes is confirmed. By means of Gaussian 98 computer program the structure, energetical features and theoretical vibrational frequencies of the complexes is calculated.